2013
DOI: 10.1089/mab.2012.0112
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate Antibodies That Specifically Bind and Neutralize CCL17 But Not CCL22

Abstract: The chemokines CCL17 (TARC) and CCL22 (MDC) function through the same receptor, CCR4, but have been proposed to differentially affect the immune response. To better understand the role of the individual ligands, a panel of rat anti-mouse CCL17 surrogate antibodies was generated that can be used to differentiate CCL17 and CCL22 function in vitro and in vivo. We have successfully identified a panel of neutralizing antibodies by screening hybridomas for the ability to inhibit CCL17-mediated calcium mobilization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…CCL17 protein was expressed in E. coli then isolated from inclusion bodies and refolded to generate functional chemokine as previously described [30]. Briefly, inclusion bodies were collected in solubilization buffer consisting of 8 M urea, 5 mM EDTA, 20 mM Tris HCl, pH 7, 10 mM DTT.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CCL17 protein was expressed in E. coli then isolated from inclusion bodies and refolded to generate functional chemokine as previously described [30]. Briefly, inclusion bodies were collected in solubilization buffer consisting of 8 M urea, 5 mM EDTA, 20 mM Tris HCl, pH 7, 10 mM DTT.…”
Section: Methodsmentioning
confidence: 99%
“…Studies blocking CCL17 in vivo are reported in the literature and these studies have been conducted using commercially available polyclonal antibodies or monoclonal rat anti-CCL17 antibody, as in the murine A. fumigatus model of invasive lung disease [12]. To study the effects of inhibiting CCL17 function in vivo , we have generated rat:mouse (IgG1) chimeric mAbs and demonstrated that upon binding CCL17 they inhibit signaling mediated through CCR4 interaction [30]. These antibodies were generated using the antigen-binding region of hybridomas from rats immunized with CCL17 and fused to mouse IgG1 Fc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since both chemokines are known to interact exclusively with CCR4, both compete for CCR4 binding and the most conserved regions are predicted to reside within the receptor binding site of each chemokine, one would expect to obtain a set of antibodies which crossreact with CCL17 and CCL22 [8,17] . Despite this, only a single dual-reactive antibody, B202, was identified in our screen, representing <1% of the entire panel [15] . In addition to binding, B202 was also shown to block CCL22 function, although this effect was weak in that only partial inhibition was evident using conditions that were sufficient to completely inhibit CCL17 function.…”
Section: Research Highlightmentioning
confidence: 94%
“…The commercially available monoclonal anti-CCL17 antibody, MAB529, is a rat IgG2a antibody that inhibits CCL17 but not CCL22 function and although useful in vitro, may complicate interpretation of in vivo results due to Fcmediated effector function. In contrast, B225 and B202 are mouse: rat chimeric antibodies such that the Fv regions are derived from rat antibodies but the Fc regions have been converted to mouse IgG1which lacks effector function [15] . This eliminates any ambiguity surrounding contribution of the rat Fc in the interpretation of in vivo findings.…”
Section: Research Highlightmentioning
confidence: 99%